The Synthesis and Properties of Asymmetrically Substituted 4,4'-Bis(1,3,5-triazine-6-yl)diaminostilbene-2,2'-disulfonic Acid Derivatives as Fluorescent Brighteners [II] - Jung, Jongkeun; Kang, Yonghan (Bulletin of the Korean Chemical Society, 2013)
In this work, the key intermediate, 4-amino-4'-(2-amino-4-anilino-1,3,5-triazine-6-yl)-aminostilbene-2,2'-disulfonic acid, was prepared from 4-(2-amino-4-anilino-1,3,5-triazine-6-yl)amino-4'-nitrostilbene-2,2'-disulfonate by using Tin(II) chloride as the reducing agent. Using this intermediate, nineteen new asymmetrically substituted bistriazinylstilbene fluorescent brightening agents were synthesized. Chemical structures of the obtained compounds 5a-s were analyzed by proton NMR spectrum. The physical properties of the new compounds 5a-s were characterized by fastness test and whiteness measurement test and the obtained data were compared to measurements obtained from CI 86. KCI Citation Count: 2